1986
DOI: 10.1111/j.1525-1470.1986.tb00519.x
|View full text |Cite
|
Sign up to set email alerts
|

A Solitary Variant of Congenital Self‐healing Reticulohistiocytosis: Solitary Hasimoto‐Prltzker Disease

Abstract: Four neonates had solitary, congenital, rapidly growing, spontaneously ulcerating tumors of the face, trunk, and extremities. No extracutaneous involvement was found, and all lesions spontaneously involuted. Mononuclear cells of the cutaneous infiltrate were Langerhans' cells. These findings expand the spectrum of congenital self-healing reticulohistiocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…This entity appears to be characterised by four features [2,14]: (1) congenital or perinatal occurrence of papules, nodules or papulovesicules; (2) in an otherwise healthy child lacking visceral involvement; (3) histopathology demonstrating an LC in®ltrate; and (4) spontaneous regression of skin lesions without recurrence.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This entity appears to be characterised by four features [2,14]: (1) congenital or perinatal occurrence of papules, nodules or papulovesicules; (2) in an otherwise healthy child lacking visceral involvement; (3) histopathology demonstrating an LC in®ltrate; and (4) spontaneous regression of skin lesions without recurrence.…”
Section: Discussionmentioning
confidence: 97%
“…While LCH con®ned to the bones or lung has long been recognized [4], it was not until 1973 that pure cutaneous LCH was described [9]. Solitary forms, such as Langerhans cell (LC) histiocytoma [2], and disseminated forms of cutaneous LCH can be distinguished. The latter were termed pure cutaneous histiocytosis X [2,23] or congenital self-healing reticulohistiocytosis (Hashimoto-Pritzker disease in recognition of the original description [9]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases of a solitary form with a single cutaneous tumor have been published. [5][6][7] Solitary CSHRH seems to contribute to approximately 25% of cases. 8 Review of the literature reveals a variety of designations for this entity that do not necessarily have to be present by birth, but may appear during early childhood (Table I).…”
mentioning
confidence: 98%
“…Ultrastructural electron microscopy study demonstrated the presence of Birbeck granules in 0–40% of the histiocytes [5, 6]. In 1986, Berger et al [7] reported the first case of a rare form of this congenital self-healing reticulohistiocytosis that occurred in a newborn, who had a solitary cutaneous nodule and no other involvement. Since then, about 30 similar cases have been reported.…”
Section: Introductionmentioning
confidence: 99%